HONEY AS A TOPICAL TREATMENT FOR DIABETIC FOOT ULCERS - Aftria, Marizka Putri (Majority, 2014)
Abstract Patients with diabetic ulcers in Indonesia is increasing, especially in the big cities and the patients need an expensive costs for therapy. That’s why we need an alternative therapy in the treatment of diabetic foot ulcers, using the traditional medicines. One of the traditional medicine which can be used to heal the ulcer is honey. Honey has peroxide hydrogen and flavanoid that function are as antiinflamation and as an antimicrobial agent effect to heal the wound. Honey can be used as an alternative therapy in the treatment of diabetic foot ulcers. Keywords: diabetic ulcer, flavonoid, honey, peroxide hydrogen Abstrak Penderita ulkus diabetik di Indonesia semakin meningkat terutama di kota besar dan memerlukan biaya yang tinggi untuk terapi. Untuk itu, diperlukan terapi alternatif dalam penyembuhan ulkus kaki diabetik, yaitu dengan menggunakan obat tradisional. Salah satu obat tradisional yang dapat digunakan untuk mengatasi luka adalah madu. Madu mengandung hidrogen peroksida dan flavanoid yang berfungsi sebagai anti inflamasi dan antimikroba sehingga terjadi penyembuhan luka. Madu dapat dijadikan terapi alternatif dalam penyembuhan ulkus kaki diabetik. Kata kunci: flavanoid, hidrogen peroksida, madu, ulkus diabetik